Assessment of practicing the professional roles and skills of the method of community organization in the field of addiction - Alqasimi, Khalid Atallah (Journal of Humanities & Social Sciences, 2022)
This study aimed to determine the extent to which professional practitioners of the method of community organization are committed to the roles of professional practice in the field of addiction, and to determine the extent to which professional practitioners of the method of community organization are committed to professional practice skills in the field of addiction. The professionals of the method of organizing society working in Irada and mental health complexes in Jeddah, Riyadh and Dammam, whose number is (89), and the study relied on the questionnaire tool to collect data. And the mediator, the enabler, and the assistant, as well as they are committed to all the professional skills they practice, such as the skill in recording, the skill in observation, the skill in building relationships with members of the community, and the skill in leadership, and that their practice of roles and professional skills for the way of organizing society in general was very high, and the study found To many recommendations, the most important of which are: holding conferences, relevant courses and workshops And financial stimulation, awareness and education of the role of the practicing social worker, developing the skills of practitioners and providing them with information that helps them in knowledge and understanding in this field because it depends on practice and experience, opening the field for external participations to raise community awareness by going to the community and creating a department for community services in addiction departments.